Effect of Cottonseed Feeding on the Body Condition Score (BCS) of Murrah Buffaloes under Different Lactation Stages (Indian Journal of Animal Production and Management, 2024)
The present study was envisaged to study  the effect of cottonseed feeding on the Body  Condition Score (BCS) of Murrah buffaloes. 54  lactating Murrah buffaloes were grouped into three  lactation groups of early (0-3 months), mid (3-6  months) and late (>6 month), each group having 18  buffaloes which were further divided into three  treatments consisting of dietary regimes of  concentrate ration containing 0% cotton seed (T1-  Control), concentrate ration containing 10%  cottonseed (T2) and concentrate ration containing  15% cottonseed (T3). The feeding trial was  performed for a period of 90 days for experimental  buffaloes under different treatments of three  different lactation stages. Fortnightly Body  Condition Scores were recorded. While there were  no significant differences in early lactation, in mid  lactation there was a significant increase in T2 while  T3 was comparable to T1, and in late lactation there  was a significant increase in T3 while T2 was similar  to control group.
Keywords: Cottonseed; BCS; Murrah buffaloes